Tweeting God : picturing the sacred in everyday life - van den Berg, Jan-Albert (Stellenbosch Theological Journal, 2019)
Elías García Martínez's "Ecco Homo" (Behold the Man), in the Sanctuary of Mercy Church in Borja, Spain, was deteriorating so rapidly that, in 2012, 81-year-old Cecilia Giménez decided to restore it. Her failed attempt led to the fresco being called "Ecco Mono" (Behold the Monkey). Due to the failed restoration attempt the artist initially faced criminal charges. However due to much interest generated from extensive media coverage and internet exposure, the artwork became a tourist attraction. Even a local wine was created to immortalise the event. In 2016, an interpretation centre for this artwork was built in Borja with the artist, Cecilia Giménez, the hero who unintendedly put her town on the proverbial world map. Pictured against the backdrop of social media, and more specifically the social media platform of Twitter, this case study serves as the focus for the research portrayed in the article, sketching the importance and meaning of everyday expressions of theology. Some of the latest developments in practical theology show similar perspectives within the domain of "lived religion" and address spiritual practices inside, but also in particular, outside the church walls as daily expressions of faith. This orientation corresponds with the notion that theological language does not exclusively belong to formal academy and the church. Daily life provides a rich canvas for incorporating various forms of "ordinary", "espoused", "implicit", "operant", "everyday", and "lived" theology and religion. The argumentation in the article is further developed by reflecting on the meaning of social media, specifically Twitter, in order to accommodate the sketching and meaning of alternative expressions of the language of faith. In the sketching of these everyday experiences of faith as portrayed in the Cecilia Giménez case study, the multi-layered beauty and sacredness of folly are illustrated.